Denúncias e anúncios: possibilidades escolares no contexto da socioeducação - Santana, Aline Neves Vieira de (2020)
The present study intends to answer the following question: which pedagogical possibilities does the State School Vida Nova - Goiânia/GO present in order to contribute and promote some life change to teenagers undergoing a social-educational internment measure? For this purpose, the overall aim of this paper is to identify how is the School structured inside the Social-educational Assistance Center of Goiânia, and the specific aims are to comprehend the role of school education (in the social-educational sphere) to the Chief juvenile court Judge of Goiânia, the Public Defenders Office of Childhood and Adolescence of Goiânia, the Social-Education Manager of the Executive Group of Support to Children and Youth, the Special Manager of Social-Education of the State Secretariat for Education, Culture and Sports and the Science teacher staff of the School; as well as to analyse the school reality of teenagers before, during and after the fulfilment of the social-educational measure of internment. This is a qualitative research, in which the Communicative Method was used, which led to data collection through Communicative Observation with the research subjects. The influence of national educational policies and everyday practices in social-education is considered through a bibliographical survey and documental analysis. It becomes clear that the infractional act leads to imprisonment in social-educational institutions and is based on legal, political, cultural, socioeconomic and racial factors, whose goal is to control and create stigma upon transgressor adolescents. By examining the reality of the State School Vida Nova, it turns out explicit that there are elements which sway and affect the structuring process of pedagogical activities developed at the School, which is headquartered in Case-Goiânia: the acknowledgement of teenagers as subjects of law; the schooling of youngsters before and during deprivation of liberty; their expectations of present and future. Some hindering elements arise: the tough life path of these teenagers; the lack of specific training and ambiance of the teachers; the curtailment of rights in the internment unit; the limits of public policies and legislation; the underperformance of the Case-Goiânia staff; the familiar routine before internment; the family’s poor level of schooling; the absence of interest for School; the precariousness of the execution of lessons in class; the redefinition and redimensioning of School and of teaching. On the other hand, some transforming elements appear too: the belief in the teenager’s life change; the commitment of the teacher towards the teenager; the understanding of the School’s relevance; the dreams that the youngster wishes to attain after the completion of the social-educational measure and the future that the teenager desires for his/her family. While society and this school paradigm in an internment institution do not change, the main proposition is to secure the teenager’s rights during the fulfillment of the social-educational measure, with special emphasis on school education. Whether it is impossible to offer schooling outside the internment unit, may the School based on this social-education system contain internal practices which humanize the human subjects and provide basic possibilities, such as reading, writing, storytelling and interpreting; and support the continuation in school after the completion of the internment measure. Current data reveal that handling the infractional act and social-education are limit situations that youngsters and their families do not want to experience again. As a product of that, there is a permission of adolescents to open up to lifechanging possibilities. However, this subject will only see new situations of inventing, creating and re-reading reality if another subject perceives him as a subject of law. It is recommended that the School redefines itself and is redefined by its peers with the further development of the Freirian methodological proposal. It encompasses the switch of conceptions about the rough life trajectories of teenagers, a new schooling curriculum and specific training of the teachers and local staff. Thus youngsters can be active in power relations that run across the in-house entrapment of this disciplinary institution and then take place within society.